English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

integrate 11sinx+12tanx


i have no idea what to do with the tan.. i know i should do something with a u ?? but .. i duno.

2007-01-11 09:00:10 · 6 answers · asked by Anonymous in Science & Mathematics Mathematics

6 answers

integral of sin x is -cos x

(integral) tan x dx = (integral) sin x /cos x dx
set
u = cos x.
then we find
du = - sin x dx

substitute du=-sin x, u=cos x

(integral) sin x /cos x dx = - (integral)
(-1) sin x dx/ cos x

= - (integral) du/ u
Solve the integral

= - ln |u| + C

substitute back u=cos x

= - ln |cos x| + C


Answer -11cos x -12ln |cos x| + C

2007-01-11 09:04:17 · answer #1 · answered by biowolf89 3 · 2 1

Let's just do ∫ tan x dx,
since that seems to be the part baffling you.
Write tan x = sin x /cos x
and notice that sin x is minus the derivative of cos x.
Thus ∫ sin x/cos x dx = - ln(cos x) + C = ln(sec x) + C,
since the integral is in the form ∫ -du/u,
with u = cos x.
BTW: Jenn gave you the derivative of tan x,
not its integral.

2007-01-11 17:13:47 · answer #2 · answered by steiner1745 7 · 0 0

well there are a couple of ways to do it...

Below is one way...

S(11sinx+12tanx)dx = S(11sinx+12(sinx/cosx))dx...

this is because tanx = sinx/cosx

now you can distribute out sinx...

it becomes,

S(11+12/cosx)sinxdx ... now you can use "u" or substitution

u = cosx and du = -sinxdx

so, the integral becomes...

-S(11+12/u)du... integrate and you get

-11u-12ln(u) + C (C being some constant)

so you sub back in cosx... and the answer is

S(11sinx+12tanx)dx = -(11cosx + 12ln(cosx)) + C = -11cosx-12ln(cosx) + C

also, -12ln(cosx) = 12ln(1/cosx) = 12ln(secx)... so the answer can be...

12ln(secx)-11cosx + C

PS The guy below me means "jenn" not me :)

2007-01-11 17:13:45 · answer #3 · answered by AresIV 4 · 0 0

write tan(x) as sin(x)/cos(x)
so we have:
sin(x)dx/cos(x)
u=cos(x)
du=-sin(x)dx
substitute in to get
-du/u
the integral of du/u is ln[abs(u)]
so -du/u -> -ln[abs(u)]
now substitute the x's back in to get:
-ln[abs(cos(x))]
that covers the tan(x) part

2007-01-11 17:11:15 · answer #4 · answered by Greg G 5 · 0 0

int. tanx = (- ln cosx )

*Edit : biowolf98 is right

2007-01-11 17:06:07 · answer #5 · answered by Psycho 3 · 0 2

-11cosx + -12secx^2

2007-01-11 17:07:51 · answer #6 · answered by j 3 · 0 6

fedest.com, questions and answers